2009
DOI: 10.1080/10538710802584635
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Characteristics, and Associations of Sexual Abuse with Sociodemographics and Consensual Sex in a Population-Based Sample of Swedish Adolescents

Abstract: The purpose of this study was to investigate lifetime prevalence and characteristics of self-reported child sexual abuse and associations between child sexual abuse, gender, sociodemographic data, and consensual sexual experiences. A questionnaire was completed by 4,339 Swedish high school seniors. Three categories of child sexual abuse were studied: noncontact, contact without penetration, and penetrating child sexual abuse. Penetrating child sexual abuse was correlated with the most severe abuse characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
47
3
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 31 publications
11
47
3
2
Order By: Relevance
“…The measures were selected on the basis of having been found to be related with sexual abuse or psychosocial health factors in the present study or in our previous studies (27,33). The variables were:…”
Section: Confounding Factorsmentioning
confidence: 99%
“…The measures were selected on the basis of having been found to be related with sexual abuse or psychosocial health factors in the present study or in our previous studies (27,33). The variables were:…”
Section: Confounding Factorsmentioning
confidence: 99%
“…Returning to the literature on child sexual abuse, it is well established that males constitute a minority of victims (e.g., Cashmore and Shackel, 2014;Finkelhor, 1994;Priebe and Svedin, 2009;Stoltenborgh et al, 2011). Diverse epidemiological studies into prevalence rates and other studies limited to pre--identified groups of victims have respectively concluded that males are at less risk of abuse than females and that they are in the minority among identified victims i (for a review see, e.g., Brayley, Cockbain & Gibson, 2014;Cashmore and Shackel, 2014;Stoltenborgh et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Recent years have seen a gradual expansion of the literature on male victims of child sexual abuse in general (see, e.g., Alaggia, 2005;Cashmore and Shackel, 2014;Edelson, 2012;Homma et al, 2012;Priebe and Svedin, 2009;Scrandis and Watt, 2014). Nonetheless, in a recent rapid evidence assessment around child sexual abuse/exploitation, most of the 184 studies covered were found to focus exclusively or overwhelmingly on female victims (Brayley, Cockbain & Gibson, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that female adolescents report sexual abuse more often than male adolescents [22,23]. Furthermore, gender differences in sexual identity development have been found among sexual-minority youth [24,25].…”
Section: Introductionmentioning
confidence: 99%